Regulating Executive Pay: Using the Tax Code to Influence Chief Executive Officer Compensation - Rose, Nancy L.; Wolfram, Catherine (Journal of Labor Economics, 2002)
This study explores corporate responses to 1993 legislation that capped the corporate tax deductibility of top management compensation not qualified as “performance‐based.” Our analysis suggests that the cap may have created a focal point for salary compensation but had little effect on total compensation levels or growth rates at firms likely to be affected by the limit. There is little evidence that the policy significantly increased the performance sensitivity of chief executive officer (CEO) pay at affected firms. We conclude that corporate pay decisions have been relatively insulated from this policy intervention.